A nuclear-localized cysteine desulfhydrase plays a role in fruit ripening in tomato. (14th December 2020) - Hu, Kang-Di; Zhang, Xiao-Yue; Yao, Gai-Fang; Rong, Yu-Lei; Ding, Chen; Tang, Jun; Yang, Feng; Huang, Zhong-Qin; Xu, Zi-Mu; Chen, Xiao-Yan; Li, Yan-Hong; Hu, Lan-Ying; et al.
Abstract: Hydrogen sulfide (H2 S) is a gaseous signaling molecule that plays multiple roles in plant development. However, whether endogenous H2 S plays a role in fruit ripening in tomato is still unknown. In this study, we show that the H2 S-producing enzyme l -cysteine desulfhydrase SlLCD1 localizes to the nucleus. By constructing mutated forms of SlLCD1, we show that the amino acid residue K24 of SlLCD1 is the key amino acid that determines nuclear localization. Silencing of SlLCD1 by TRV-SlLCD1 accelerated fruit ripening and reduced H2 S production compared with the control. A SlLCD1 gene-edited mutant obtained through CRISPR/Cas9 modification displayed a slightly dwarfed phenotype and accelerated fruit ripening. This mutant also showed increased cysteine content and produced less H2 S, suggesting a role of SlLCD1 in H2 S generation. Chlorophyll degradation and carotenoid accumulation were enhanced in the SlLCD1 mutant. Other ripening-related genes that play roles in chlorophyll degradation, carotenoid biosynthesis, cell wall degradation, ethylene biosynthesis, and the ethylene signaling pathway were enhanced at the transcriptional level in the lcd1 mutant. Total RNA was sequenced from unripe tomato fruit treated with exogenous H2 S, and transcriptome analysis showed that ripening-related gene expression was suppressed. Based on the results for a SlLCD1 gene-edited mutant and exogenous H2 S application, we propose that the nuclear-localized cysteine desulfhydrase SlLCD1 is required for endogenous H2 S generation and participates in the regulation of tomato fruit ripening.